2014
DOI: 10.1902/jop.2013.130205
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing in Improving Oral Health: A Systematic Review of Randomized Controlled Trials

Abstract: Reviewed randomized controlled trials showed varied success of MI in improving oral health. The potential of MI in dental health care, especially on improving periodontal health, remains controversial. Additional studies with methodologic rigor are needed for a better understanding of the roles of MI in dental practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
131
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(139 citation statements)
references
References 35 publications
1
131
0
7
Order By: Relevance
“…In such a disease with multifactorial etiologies and complex treatment strategies [3,4], very few studies have focused on the role of motivation in dental treatment seeking behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a disease with multifactorial etiologies and complex treatment strategies [3,4], very few studies have focused on the role of motivation in dental treatment seeking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al [4] assessed the effect of motivational interviewing (MI) in improving oral health through a systematic review and found that four studies reported positive effects of MI on oral health outcomes whereas another four showed null effect. The study emphasized on the need for further studies with methodological rigor for a better understanding of the roles of MI in dental practice.…”
Section: Introductionmentioning
confidence: 99%
“…Of the eight articles in this review, only two use an MI-based approach and both were included in the review by Gao et al in 2013, 2 thus not contributing new knowledge on the theme. Kopp et al 5 included five articles in their analysis, of which only one differed from those in the review by Gao et al 2 All the studies obtained a good quality assessment. Two articles showed no influence of MI on the clinical results of patients, while the other three demonstrated that the use of MI as an adjunct to periodontal treatment resulted in significantly higher clinical outcome values compared to controls or improvement in self-efficacy for dental hygiene.…”
Section: Referencesmentioning
confidence: 99%
“…Gao et al 2 published the first literature review relating MI and oral health, which remains the broadest and most comprehensive to date. The quality of the 16 studies includeddivided into 20 articles -was assessed on a 21-point scale and included an objective evaluation of topics that analyzed everything from how clearly the objective was defined to calculating losses.…”
mentioning
confidence: 99%
“…확대되어가고 있다 [10][11][12][13] We need collaboration between the patient and clinician. 0.822 We need internal motivation rather than attempting to persuade or instill motivation from the outside.…”
mentioning
confidence: 99%